2009
DOI: 10.1007/s12024-009-9134-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of retinal hemorrhage in abusive head trauma

Abstract: Abusive head injury, characterized by repeated acceleration-deceleration forces, is associated with retinal hemorrhages as demonstrated in many clinical and postmortem studies. The theory that vitreoretinal traction is the major factor in the pathogenesis of retinal hemorrhages is presently the most widely accepted explanation based on different lines of research. Postmortem examination of the eye and orbital structures is essential for recognizing abusive head injury and also for identifying other possible me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Two main mechanisms are proposed: The first is venous outflow obstruction in raised intracranial or intravascular pressure; the second is mechanical, commonly referred to as vitreo-retinal traction (Wygnanski-Jaffe et al. 2009 ). Pathological studies indicate that venous stasis and leakage from retinal vessels are a more likely cause of retinal bleeding than vitreo-retinal traction (Emerson et al.…”
Section: Shaken Baby Syndromementioning
confidence: 99%
“…Two main mechanisms are proposed: The first is venous outflow obstruction in raised intracranial or intravascular pressure; the second is mechanical, commonly referred to as vitreo-retinal traction (Wygnanski-Jaffe et al. 2009 ). Pathological studies indicate that venous stasis and leakage from retinal vessels are a more likely cause of retinal bleeding than vitreo-retinal traction (Emerson et al.…”
Section: Shaken Baby Syndromementioning
confidence: 99%
“…2 Furthermore, it has been suggested that almost a third of AHT cases are not identified on initial presentation to a health-care professional, especially since external evidence may not be present. 3 Consequently, there is a need for a novel framework that enables these specialists to identify the clinical signs of this injury competently in order to ensure swift action can be taken to safeguard the child.…”
Section: Introductionmentioning
confidence: 99%
“…Along with damages such as subdural hematomas or diffuse axonal injuries, SBS/AHT is often accompanied by retinal hemorrhages (RHs). RHs are empirically regarded as an important symptom to distinguish abuse from accident because it is seen in approximately 85% of the victims of SBS/ AHT whereas it is observed under accidental context only with decisive external injuries such as those in fatal motor vehicle accidents (Wygnanski-Jaffe et al, 2009). In contrast to the term SBS, the term AHT does not require shaking as a necessary factor, but shaking is still considered as a very major factor.…”
Section: Introductionmentioning
confidence: 99%